1996
DOI: 10.1021/bi9517493
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Soluble Adrenal Phosphatidylinositol 4-Kinase Reveals Wortmannin Sensitivity of Type III Phosphatidylinositol Kinases

Abstract: Phosphorylation of phosphatidylinositol (PtdIns) by PtdIns 4-kinases is the first step in the synthesis of polyphosphoinositides, the lipid precursors of intracellular signaling molecules. We have recently identified a cytosolic PtdIns 4-kinase (cPI4K) in the bovine adrenal cortex that is distinguished from previously known PtdIns 4-kinases by its sensitivity to the PtdIns 3-kinase inhibitor wortmannin (WT). The present study has further characterized this soluble enzyme and compared its properties to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
83
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 39 publications
14
83
0
Order By: Relevance
“…Recent studies have shown that other kinases, including PI4K (65)(66)(67)(68), are also susceptible to inhibition by both LY294002 and Wortmannin at concentrations in excess of those required for inhibition of PI3K. To further confirm our results and to gain further insight into the mechanism by which the PI3K modulates p27…”
Section: P27supporting
confidence: 77%
“…Recent studies have shown that other kinases, including PI4K (65)(66)(67)(68), are also susceptible to inhibition by both LY294002 and Wortmannin at concentrations in excess of those required for inhibition of PI3K. To further confirm our results and to gain further insight into the mechanism by which the PI3K modulates p27…”
Section: P27supporting
confidence: 77%
“…PI4KIII types α and β are present in the cytoplasm, plasma membrane, the Golgi, and the nucleolus. Considering the importance of PI4KIIIα in maintaining PM PI(4)P (16) and its potent inhibition by wortmannin (44,45), the small size of the wortmannin effect on KCNQ2/3 currents (only a 15% decrease) is more puzzling. One possible explanation would be that following PI4KIII inhibition there is a compensatory slowing of lipid phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…We asked whether both classes of PI 4-kinase contribute precursor PI(4)P that ultimately enters the PM PI(4,5)P 2 pool. As general blockers of each class of PI 4-kinase, we used the type IIα and type IIβ inhibitor cytosolic adenosine (25,44) (13,14,16,23,30,45). In control experiments, the KCNQ2/3 current is quite stable during 500 s of whole-cell recording (Fig.…”
Section: C-f)mentioning
confidence: 99%
“…Concentrations of wortmannin 100-fold greater than those required to inhibit phosphatidylinositol 3-kinase (10 -100 nM) are reported to inhibit phosphatidylinositol 4-kinase (10 -100 M) (35). PIP is the immediate precursor of PIP 2 , which is the substrate for PLC and the precursor of IP 3 (36).…”
Section: Inhibition Of Ip 3 Receptor Function With 2-apb But Not Hepmentioning
confidence: 99%